Cell Wall Composition as a Marker of the Reprogramming of the Cell Fate on the Example of a Daucus carota (L.) Hypocotyl in Which Somatic Embryogenesis Was Induced - Kuczak, Michał (Int J Mol Sci, 2020)
Changes in the composition of the cell walls are postulated to accompany changes in the cell’s fate. We check whether there is a relationship between the presence of selected pectic, arabinogalactan proteins (AGPs), and extensins epitopes and changes in cell reprogramming in order to answer the question of whether they can be markers accompanying changes of cell fate. Selected antibodies were used for spatio-temporal immunolocalization of wall components during the induction of somatic embryogenesis. Based on the obtained results, it can be concluded that (1) the LM6 (pectic), LM2 (AGPs) epitopes are positive markers, but the LM5, LM19 (pectic), JIM8, JIM13 (AGPs) epitopes are negative markers of cells reprogramming to the meristematic/pluripotent state; (2) the LM8 (pectic), JIM8, JIM13, LM2 (AGPs) and JIM11 (extensin) epitopes are positive markers, but LM6 (pectic) epitope is negative marker of cells undergoing detachment; (3) JIM4 (AGPs) is a positive marker, but LM5 (pectic), JIM8, JIM13, LM2 (AGPs) are negative markers for pericycle cells on the xylem pole; (4) LM19, LM20 (pectic), JIM13, LM2 (AGPs) are constitutive wall components, but LM6, LM8 (pectic), JIM4, JIM8, JIM16 (AGPs), JIM11, JIM12 and JIM20 (extensins) are not constitutive wall components; (5) the extensins do not contribute to the cell reprogramming.